Analysis of Students' High Order Thinking Skills in Vertical Motion Concept - Muhammad Wildan Firdaus; Ugan Sugandi; Diah Mulhayatiah; Muhammad Minan Chusni (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2022)
One indication of advancement and change in the world of education is the growth of the learning process. Education is a key indicator of a nation's development, particularly in Indonesia. Physics is a very essential topic, and its changes are readily apparent, particularly in school-based learning activities. It is believed that physics learning activities need to be enhanced in order to produce a more intelligent and competitive generation. The improvement can be started from providing better materials and concepts, one of which is by implementing Higher Order Thinking Skills (HOTS) learning activities by emphasizing critical thinking skills and problem-solving skills, it is hoped that students can be more active and creative in participating in the learning process. The purpose of this article is to determine the effect of questions and worksheets that are integrated with Higher Order Thinking Skills (HOTS) on students' critical thinking skills. The results of the study show that 80% of students can complete physics calculations. However, students have difficulty in interpreting the data provided. The conclusion is that the higher order thinking ability (HOTS) of students is still low in the evaluation category. Because the data found that students were only able to complete physics calculations (inference) but were not able to interpret the answers (evaluation).